Seismic geomorphology of cretaceous megaslides offshore Namibia (Orange Basin): Insights into segmentation and degradation of gravity-driven linked systems - Scarselli, N.; McClay, K.; Elders, Chris (Elsevier, 2016)
This study applies modern seismic geomorphology techniques to deep-water collapse features in the Orange Basin (Namibian margin, Southwest Africa) in order to provide unprecedented insights into the segmentation and degradation processes of gravity-driven linked systems. The seismic analysis was carried out using a high-quality, depth-migrated 3D volume that images the Upper Cretaceous post-rift succession of the basin, where two buried collapse features with strongly contrasting seismic expression are observed. The lower Megaslide Complex is a typical margin-scale, extensional-contractional gravity-driven linked system that deformed at least 2 km of post-rift section. The complex is laterally segmented into scoop-shaped megaslides up to 20 km wide that extend downdip for distances in excess of 30 km. The megaslides comprise extensional headwall fault systems with associated 3D rollover structures and thrust imbricates at their toes. Lateral segmentation occurs along sidewall fault systems which, in the proximal part of the megaslides, exhibit oblique extensional motion and define horst structures up to 6 km wide between individual megaslides. In the toe areas, reverse slip along these same sidewall faults, creates lateral ramps with hanging wall thrust-related folds up to 2 km wide. Headwall rollover anticlines, sidewall horsts and ramp anticlines may represent novel traps for hydrocarbon exploration on the Namibian margin.The Megaslide Complex is unconformably overlain by few hundreds of metres of highly contorted strata which define an upper Slump Complex. Combined seismic attributes and detailed seismic facies analysis allowed mapping of headscarps, thrust imbrications and longitudinal shear zones within the Slump Complex that indicate a dominantly downslope movement of a number of coalesced collapse systems. Spatial and stratal relationships between these shallow failures and the underlying megaslides suggest that the Slump Complex was likely triggered by the development of topography created by the activation of the main structural elements of the lower Megaslide Complex. This study reveals that gravity-driven linked systems undergo lateral segmentation during their evolution, and that their upper section can become unstable, favouring the initiation of a number of shallow failures that produce widespread degradation of the underlying megaslide structures. Gravity-driven linked systems along other margins are likely to share similar processes of segmentation and degradation, implying that the megaslide-related, hydrocarbon trapping structures discovered in the Namibian margin may be common elsewhere, making megaslides an attractive element of deep-water exploration along other gravitationally unstable margins.